Carbon and nitrogen in a Ferralsol under zero‐tillage rotations based on cover, cash or hay crops. (4th February 2015) - Alburquerque, M. A.; Dieckow, J.; Sordi, A.; Piva, J. T.; Bayer, C.; Molin, R.; Pergher, M.; Ribeiro‐Junior, P. J.; Goss, Michael
Abstract To identify crop rotation systems capable of sequestering C and N to 1 metre depth in a subtropical Ferralsol of Southern Brazil managed under long‐term zero‐tillage (21 yrs), we evaluated six crop sequences: wheat (Triticum aestivum)–soybean (Glycine max) [W‐S], the baseline; oat (Avena strigosa, as cover crop)–maize (Zea mays)–wheat–soybean [O‐M‐W‐S]; vetch (Vicia villosa, as legume cover crop)–maize–wheat–soybean [V‐M‐W‐S]; vetch–maize–oat–soybean–wheat–soybean [V‐M‐O‐S‐W‐S]; ryegrass (Lolium multiflorum, for hay)–maize–ryegrass–soybean [R‐M‐R‐S]; and alfalfa (Medicago sativa, for hay)–maize [A‐M]. Compared to W‐S and to 1 metre, the hay‐based system of A‐M showed the largest C and N sequestration rates (0.50 and 0.06 Mg/ha/yr, respectively). Alfalfa, being a perennial legume under cut‐regrowth cycles, possibly added more C and N through roots. The other hay system, R‐M‐R‐S, also sequestered C efficiently (0.27 Mg/ha/yr), but not N (0.01 Mg/ha/yr). The legume‐based system of V‐M‐W‐S sequestered significant amounts of both C (0.29 Mg/ha/yr) and N (0.04 Mg/ha/yr). The grass‐based system of O‐M‐W‐S showed the lowest sequestration of C (0.09 Mg/ha/yr). In all systems, a positive relationship (R2 = 0.71) occurred between estimated addition of root C and soil C stock to 1 metre. Whenever C and N sequestration occurred, more than half of that occurred below 20 cm depth. Results suggest that adoption of legume‐based systems, perennially as A‐M or annually as V‐M‐W‐S, is efficient for C and N sequestration in subtropical zero‐tillage soils and that roots possibly contribute more to that sequestration than aboveground biomass.